Radioiodine therapy in the different stages of differentiated thyroid cancer. Issue 1 (January 2023) - Valerio, Laura; Maino, Fabio; Castagna, Maria Grazia; Pacini, Furio
Abstract : Differentiated thyroid cancer is the most frequent type of thyroid cancer with an increasing incidence in the last decades. The initial management is represented by surgical treatment followed by radioactive iodine therapy that includes remnant ablation, adjuvant treatment or treatment of metastatic disease. Radioactive iodine treatment is performed only in selected cases based on the risk of recurrence and mortality during follow up, according to American Joint Committee on Cancer Union for international Cancer Control Tumor, Node, Metastasis (AJCC/TNM) staging system and the 2015 American Thyroid Association (ATA) risk stratification system. This article will review the key factors to consider when planning radioactive iodine therapy in differentiated thyroid cancer patients after surgery and during follow up.